Renovatio imperii Romani: krikščioniškosios pasaulėžiūros dėmuo - Ščavinskas, Marius (Lietuvos istorijos studijos, 2003)
There have not been any researches on the Medieval Christian world outlook done in Lithuania at all. A bit more attention was given to such problems as interaction of ancient Balts with Christian culture, Baltic view at Christianity. Usually, those topics are squeezed into the XIII-XIV century frame, which is more actual. Recently, scholars succeeded in grounding the conceptuality of 1009 in historiography. In this context, renovatio conception was determined, however mostly meaning its political expression. But also not less important is the portend of Christian world outlook in renovatio policy, beginning with Charlemagne and ending with the most significant person in this policy—Otto III. The political expression and dimension of Otto’s renovatio conception are clear enough: the emperor is christomimetes on the earth, his power comes out of Dei gratia, and he rules all over the Christian world. The emperor appoints popes and bishops, organizes missions (this is connected or bounded up with conditionally weak, if compared to emperor’s, papal power in the VIII-XI centuries). Another one of the most important goals of renovatio is to make conditions for old and newly-risen countries of Central and Eastern Europe (firstly Hungary and Poland) to become a part of the federation created by Otto. They were supposed to become rulers of certain federal subjects, allies of the emperor, who could help in the restoration of the whole empire, who could expand and praise it. The Christian world outlook is also very important. It let Otto settle himself into the existence of christomimetes, by using this to declare the emperor’s responsibility to expand Christianity in pagan lands, and responsibility for the salvation of every Christian soul. Those facts explain such missions to Baltic lands as the mission of St. Adalbert-Wojciech, St. Bruno of Querfurt, and the mission of 5 Benedictine monks. All of them were organized by Otto (until Dictatus papae). Renovatio policy served as a tool for Otto to get the whole world under his crown (including the Byzantine emperor and Kiev Russia). Inversely, Otto shows that his empire is not civitas terrena or civitas diaboli—according to St. Augustine, who thought that the fight for the salvation of souls was going on the earth and in "another" world as eschatology minor. The emperor identified himself with christomimetes, which meant that his country couldn’t be identified with civitas diaboli any more. Civitas terrena was a temporary shelter for a man. The same temporality is waiting for a soul in the "another world" until the day of the Last Judgment. Only after the Last Judgment will it become clear where which soul will be going—to hell or paradise. Only good behavior and good works dedicated to soul and body helped people to achieve eternal life. The formation of such behavior was one of the main tasks and functions of the emperor. In conclusion, the idea of federation, as much as the Christian view, formed conditions for peaceful missions in Eastern Europe. Military actions began much later. They are connected with changes in the Church’s life after the announcing of Dictatus papae, also with changes in the world outlook and events in the Holy Land, which led to the beginning of the Crusades.